Epidemiological determinants and clinical profile of eclampsia: a case control study - De, Ritam; Dutta, Amit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The incidence of eclampsia has reduced considerably in the developing countries due to good antenatal care and increased awareness within the population. To determine the magnitude of the problem, to assess trends and to identify risk factors and risk groups, it is worthwhile to periodically review this problem. Methods: A study using one control for each case of eclampsia was conducted among women who were admitted at Burdwan Medical College and Hospital between July 2014 and June 2015. Cases were women with a confirmed diagnosis of eclampsia. Eclampsia cases were identified by daily monitoring of all new admissions to Eclampsia ward of Burdwan Medical College and hospital. After strict exclusion criteria, a total of 500 eclampsia cases were studied along with same number of controls for identifying the epidemiological determinants. Results: Maternal age at extremes (<20 and >30 years) was identified as a risk factor of eclampsia. Nulliparity has been identified as a risk factor for eclampsia in present study. About 74.6% mothers were nulliparous. Most of the patients 66.6% were admitted during the antenatal period i.e. presented with antenatal eclampsia. 62.2% of them were at between 34-37weeks of gestational age during admission. Conclusions: Authors observed increased eclampsia risk among women with a prior history of pregnancies complicated by hypertensive disorders. Positive personal histories of hypertensive disorders of pregnancy and family history of hypertensive disorders are well known risk factors of eclampsia. Our findings point to public health and clinical measures that may be taken to potentially attenuate the incidence of eclampsia and mitigate associated maternal-fetal complications resulting from the disorder.